2020
DOI: 10.1038/s41598-020-76464-w
|View full text |Cite
|
Sign up to set email alerts
|

The surface modification and characterization of SiO2 nanoparticles for higher foam stability

Abstract: The surfactant and colloidal nanoparticles has been considered for various applications because of interaction of both complex mixtures. The hydrophilic SiO2 nanoparticle could not be surface active behavior at the liquid/air interface. In this study, the SiO2 nanoparticles have been modified with 3-isocyanatopropyltriethoxy-silane (ICP), and the effect of foam stability has been investigated. The physical properties of surface modified SiO2 nanoparticle were analyzed by XRD, TGA, FT-IR, and SEM. After surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 25 publications
(26 reference statements)
1
23
0
Order By: Relevance
“…We then prepared carboxyl-labeled SiO 2 NPs using the modified Stöber method . The X-ray diffraction (XRD) patterns of the synthesized SiO 2 NPs (Figure S4a) show they are amorphous, consistent with previous reports . Dynamic light scattering (DLS) revealed that the SiO 2 NPs had a hydrodynamic diameter of 150 ± 10 nm (Figure S4b).…”
Section: Legumain-mediated Aggregation Of P-sio2 Nps In Vitrosupporting
confidence: 85%
See 1 more Smart Citation
“…We then prepared carboxyl-labeled SiO 2 NPs using the modified Stöber method . The X-ray diffraction (XRD) patterns of the synthesized SiO 2 NPs (Figure S4a) show they are amorphous, consistent with previous reports . Dynamic light scattering (DLS) revealed that the SiO 2 NPs had a hydrodynamic diameter of 150 ± 10 nm (Figure S4b).…”
Section: Legumain-mediated Aggregation Of P-sio2 Nps In Vitrosupporting
confidence: 85%
“…46 The X-ray diffraction (XRD) patterns of the synthesized SiO 2 NPs (Figure S4a) show they are amorphous, consistent with previous reports. 47 Dynamic light scattering (DLS) revealed that the SiO 2 NPs had a hydrodynamic diameter of 150 ± 10 nm (Figure S4b). Structural characterization of these structures with scanning electron microscopy (SEM) confirmed the formation of uniform spherical SiO 2 NPs (Figure S4c, S 4d).…”
Section: Nps In Vitromentioning
confidence: 99%
“…There were three ways of creating silica-based nanofillers in this paper. The first was surface modified solid nanoparticles (fumed silica, AEROSIL 200) via functional silane; the second was nanoparticles generated by core–shell copolymerization from colloidal silica (Grace LUDOX AM) and functional silane; the third was nanoparticles and/or their graft copolymers generated by the sol–gel process of tetraethyl orthosilicate (TEOS) and functional silane . Six basic polymers (303-POSS, 3F-303-polymer, C8-303-polymer, 402-polymer, 3F-402-polymer, and C8-402-polymer) were synthesized through a sol–gel method, and the derivative (amino-PDMS)-(303-POSS) polymer was synthesized by an epoxy ring-opening reaction with amino groups.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 3A shows the XRD patterns taken from SiO 2 and H‐ZSM‐5 as reference for support samples. The diffraction pattern of SiO 2 present the profile of an amorphous phase with a broad shallow peak centered at 2θ to 22° (JCPDS 29‐0085) 46 . In contrast, the XRD pattern of H‐ZSM‐5 sample display sharp peaks at 2θ = 7.9°, 9.04°, 13.59°, 14.19°, 15.14°, 15.91°, 23.38°, 24.16°, and 25.63°.…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction pattern of SiO 2 present the profile of an amorphous phase with a broad shallow peak centered at 2θ to 22 (JCPDS 29-0085). 46 In contrast, the XRD pattern of H-ZSM-5 sample display sharp peaks at 2θ = 7. 47 The XRD pattern of SiO 2 and H-ZSM-5, shown in Figure 3A, shows no other impurity peaks, indicating the high purity of the support samples.…”
Section: Xrd Patterns Of the Fresh Catalystsmentioning
confidence: 93%